On language - Chomsky, Noam. ([S.l.] : Penguin Books India Pvt Ltd, 2003)
Chomskys classic works language and responsibility and responsibility on language in one volume on language restores to print two of chomskys most famous and popular books in one omnibus editionlanguage and responsibility and reflections on language in language and responsibility, chomsky presents a fascinating self-portrait of his political, moral and linguistic thinking in reflections on language, he explores the more general implications of the study of language and offers incisive analyses of the controversies among psychologists, philosophers and linguists over fundamental questions of language featuring some of the noted linguist and political critics most informal and highly accessible work, this book is an ideal introduction to his thought.
Keywords: Chomsky, Noam; Generative grammar; Grammar, Comparative and general; Language and languages; Language and languages--Political aspects; Linguistics; Political and social views